Al–Ge–Al Nanowire Heterostructure: From Single‐Hole Quantum Dot to Josephson Effect. Issue 39 (8th August 2021) - Delaforce, Jovian; Sistani, Masiar; Kramer, Roman B. G.; Luong, Minh A.; Roch, Nicolas; Weber, Walter M.; den Hertog, Martien I.; Robin, Eric; Naud, Cecile; Lugstein, Alois; Buisson, Olivier
Abstract: Superconductor–semiconductor–superconductor heterostructures are attractive for both fundamental studies of quantum phenomena in low‐dimensional hybrid systems as well as for future high‐performance low power dissipating nanoelectronic and quantum devices. In this work, ultrascaled monolithic Al–Ge–Al nanowire heterostructures featuring monocrystalline Al leads and abrupt metal–semiconductor interfaces are used to probe the low‐temperature transport in intrinsic Ge (i‐Ge) quantum dots. In particular, demonstrating the ability to tune the Ge quantum dot device from completely insulating, through a single‐hole‐filling quantum dot regime, to a supercurrent regime, resembling a Josephson field effect transistor with a maximum critical current of 10 nA at a temperature of 390 mK. The realization of a Josephson field‐effect transistor with high junction transparency provides a mechanism to study sub‐gap transport mediated by Andreev states. The presented results reveal a promising intrinsic Ge‐based architecture for hybrid superconductor–semiconductor devices for the study of Majorana zero modes and key components of quantum computing such as gatemons or gate tunable superconducting quantum interference devices. Abstract : A highly tunable superconducting–semiconducting hybrid junction based on intrinsic germanium (i‐Ge) nanowires is revealed. Low‐temperature transport measurements of ultrascaled monolithic Al–Ge–Al nanowire heterostructures featuring monocrystalline Al leads and abrupt Al–Ge interfaces demonstrate that such i‐Ge quantum dot devices can be tuned to access three distinct regimes: single‐hole‐filling quantum dots, an intermediate sub‐gap states regime, and a superconducting regime.